Pengaruh Adopsi International Financial Reporting Standard (IFRS) Terhadap Manajemen Laba Dengan Kualitas Audit Sebagai Variabel Moderasi Pada Perusahaan Perbankan Di Bursa Efek Indonesia - ., Sutarti; Anggwikara, Sherly (Jurnal Ilmiah Akuntansi Kesatuan, 2018)
The term earnings management arises as a direct consequence of the efforts of managers performing management accounting information, particularly relating to income (earnings). Earning management can not be categorized as a negative because earnings management is not always related to earnings manipulation. At the same time, Indonesia is required to abide by the development of IFRS-based accounting standards. It aims to improve the reliability, fairness, and transparency of financial statements in accordance with international accounting standards.The purpose of this study was (1) to determine how to measure earnings management in the banking company, (2) to determine whether or not the effect of the adoption of IFRS on earnings management, as well as to determine the effect of IFRS adoption when using variable moderation. Moderating variables used in this study include the quality of the audit, while the control variables are firm size, leverage, and operating cash flow. The research on banking companies in Indonesia Stock Exchange as many as 25 companies with a term of five years from the year 2009 to 2013 financial reporting. Data collected by collecting all the financial statements that the research samples that can diakes through IDX website. This study analysis uses multiple regression analysis with SPSS 17. Results showed there were positive effects of the adoption of IFRS on earnings management. Audit quality has a negative effect. The size of the company has a negative effect on earnings management. Leverage is measured by using a formula of debt to equity, showing the results of positive effect on earnings management.